Fertilizantes orgânicos: Índice de eficiência e produção de alface, cenoura e mudas de eucalipto - Eckhardt, Daniel Pazzini (2015)
The process of transformation and stabilization of organic materials, like traditional compost and vermicompost, increase the efficiency of biofertilizers production. This work aimed to quantify the N mineralization and the P and K availability from cattle manure fertilizers such as evaluate the responses of lettuce (Lactuca sativa L.), carrot (Daucus carota L.) and eucalyptus seedling (Eucalyptus urograndis) to them. The efficiency index and the mineralization of N and the availability of P and K was measured in five organic fertilizers: vermicompost of cattle manure mixed with straw of pasture (VEB); compost of cattle manure and straw (CEBP); cattle manure from confinement (EBC); manure of dairy cattle in nature (EBL); high humidity vermicompost (VEU). Mineralization and efficiency index of P were improve by vermicomposting. Availability of K was improve by cattle manure in nature and the efficiency index was improve by vermicomposting with high moisture and artificial airflow. In lettuce and carrot production four fertilizers was use: VEB, CEBP, cattle manure (EB) and urea, in six doses: 0, 33, 66, 100, 133 and 166% of N recommendation to lettuce and carrot production. By carrot production, only mineral fertilization was reapply. On lettuce, cattle manure vermicompost increases the production of green matter, dry matter, total number of leaves and commercial leaves, such as fresh root weight, root length and root diameter increases on carrot. Four fertilizers was use on eucalyptus seedlings: VEB, CEBP, EB and a commercial product, in five doses (v/v): 20, 40, 60, 80 and 100%. Doses from 20 to 80% of cattle manure and doses of 40 to 100% of cattle manure vermicompost and compost of cattle manure with straw improves eucalyptus seedlings development. Therefore, organic fertilizers obtained from cattle manure are efficient on lettuce, carrot and eucalyptus seedling production.